Physical Fitness of Adolescent Smoker (KEMAS: Jurnal Kesehatan Masyarakat, 2019)
Adolescent smoking behavior has a bad influence on health and fitness. The purpose of this study was to determine vital capacity and hemoglobin level in smoker and non-smoker adolescent towards physical fitness. The study was quantitative research with surveys and measurement tests. The sample size was 40 adolescents which in the neighborhood of Gunungpati. We used t-test, MANOVA and post hoc test to determine the differences in smoker and non-smoker adolescent. This study showed smoker adolescents had lower vital capacity compared than non-smoker adolescents. The value of hemoglobin levels in smoker adolescents were higher than non-smoker adolescents so that it affect the low levels of physical fitness. For adolescents, it is expected to maintain physical fitness through physical activity and reduce the number of cigarettes consumed and even try to stop smoking for smoker adolescents..